Foreign Aid and Child Mortality Rate in Nigeria - Funmilola Bukola Adebanji; Philip Ifeakachukwu Nwosa; Olusoji Ojo; Olamide Jacquilyne Alake (Signifikan: Jurnal Ilmu Ekonomi, 2020)
Several factors have attributed to the high child mortality rate, including poverty, age of women at birth, and length of the interval between births. Besides, the lack of financial resources in developing countries has been a challenge in addressing the prevalent high child mortality rate. Thus, this study seeks to examine the relationship between foreign aid and infant mortality in Nigeria from 1981 to 2018. Employing Auto-Regressive Distributed Lag (ARDL) technique, the study observed that foreign aid, government expenditure on health, real GDP, and carbon dioxide emission negatively impacted child mortality. Hence, the study concludes that foreign aid reduces child mortality in Nigeria. The study recommends that the government ensure that all foreign aid and grants use immediately to reduce child mortality by building the necessary infrastructure and making it readily available.JEL Classification: F35, I19.How to Cite:Adebanji, F. B., Nwosa, P. I., Ojo, O. O., & Alake, O. J. (2020). Foreign Aid and Child Mortality Rate in Nigeria. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 187-194.  https://doi.org/10.15408/sjie.v9i2.14960.